Empowering Performance: How Compensation and Motivation Influence Employees at PT. Pelita Abadi Sejahtera Cirebon - Riswanto, Tiyo; Jamaludin, Asep; Nandang, Nandang (Lembaga Riset dan Inovasi Al-Matani, 2024)
This research aims to: (1) analyze, understand, and explain compensation at PT Pelita Abadi Sejahtera; (2) analyze, understand, and explain motivation at PT Pelita Abadi Sejahtera; (3) analyze, understand, and explain employee performance at PT Pelita Abadi Sejahtera; (4) analyze, understand, and explain the relationship between compensation and motivation with employee performance at PT Pelita Abadi Sejahtera; (5) analyze, understand, and explain the effect of compensation on employee performance at PT Pelita Abadi Sejahtera; (6) analyze, understand, and explain the effect of motivation on employee performance at PT Pelita Abadi Sejahtera; and (7) analyze, understand, and explain the combined effect of compensation and motivation on employee performance at PT Pelita Abadi Sejahtera. The study utilizes a descriptive method to describe issues related to the independent variables—compensation, work motivation, and employee performance. The verification approach is used to assess the effects of compensation and work motivation on employee performance. The population consists of employees at PT Pelita Abadi Sejahtera Cirebon in the second process section, with a total sample of 67 employees selected using nonprobability sampling. Path analysis is employed as the analytical tool. The results reveal: (1) a very strong and positive correlation between the compensation variable (X1) and work motivation (X2), with a correlation coefficient of 0.808; (2) no partial effect of compensation (X1) on employee performance (Y), where compensation contributes 10.28% to employee performance; (3) a partial effect of work motivation (X2) on employee performance (Y), with work motivation influencing employee performance by 84.76%; and (4) a significant simultaneous effect of compensation (X1) and work motivation (X2) on employee performance (Y), accounting for 95.03%, with the remaining impact attributable to other factors.